Beyond Scientificity: Extensions and Diffractions in Post-Normal Science’s Ethos - Kastenhofer, Karen (Serendipities. Journal for the Sociology and History of the Social Sciences, 2022)
Sixty years have passed since Merton’s famous publication of “a note on science and democracy,” outlining the scientific ethos via four sets of norms, namely communism, universalism, disinterestedness, and organized skepticism (CUDOS). Merton’s rationale was that the implementation of this ethos was instrumental in realizing science’s institutional goal: “the extension of certified knowledge.” Throughout the ensuing decades, Merton’s conception has been at the center of heated debates in the emerging field of science and technology studies. It has also been addressed by empirical studies with a view to determine the scale at which CUDOS was supported by scientists themselves in explicit terms and/or conformed to in their actual practice. Some of these studies also make room for the possibility that CUDOS might have evolved throughout the past decades, incrementally adapting the norm sets. This article contributes to such empirical endeavors. Building on ethnographic work at a technology assessment (TA) institute, I find that a distinct shared ethos is tangible in TA’s post-normal science practices—in collaborations with non-scientists as well as with “pure academics.” A reconstruction of TA’s distinct ethos from my empirical material results in the delineation of a post-normal scientific ethos, comprising “extended communism,” “diffracted universalism,” “diffracted disinterestedness,” “extended organized skepticism,” “diffracted originality,” and “extended relevance.” These “extensions” and “diffractions” have ramifications for the organization of post-normal science and its interaction with academia, publics, and polities.